2017
DOI: 10.1007/5584_2017_38
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Due to Nosocomial Infection with Klebsiella pneumoniae ESBL+

Abstract: Klebsiella pneumoniae is one of the most important hospital pathogens, particularly concerning the multidrug-resistant strain ESBL. The aim of this study was to evaluate nosocomial infections with K. pneumoniae ESBL in the context of infection location, risk factors, and prognosis. This hospital study was conducted retrospectively and covered a 3 months' period. The infection with K. pneumoniae ESBL was diagnosed in 36 patients (19 women and 17 men) of the mean age of 74.2 ± 14.8 years. The number of infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It has recently been demonstrated that Klebsiella is capable of exploiting pioneer communities in the premature infant gut and establishes during later periods of microbial succession ( Rao et al., 2021 ), though the mechanisms underlying this remain unknown. Klebsiella has previously been associated with sepsis, necrotizing enterocolitis (NEC), and nosocomial infections in neonates ( Starzyk-Łuszcz et al., 2017 ; Wisgrill et al., 2019 ). Multidrug-resistant and hyper-virulent Klebsiella has emerged globally and is now a major cause of severe infections, particularly in immuno-compromised patients ( Lee et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that Klebsiella is capable of exploiting pioneer communities in the premature infant gut and establishes during later periods of microbial succession ( Rao et al., 2021 ), though the mechanisms underlying this remain unknown. Klebsiella has previously been associated with sepsis, necrotizing enterocolitis (NEC), and nosocomial infections in neonates ( Starzyk-Łuszcz et al., 2017 ; Wisgrill et al., 2019 ). Multidrug-resistant and hyper-virulent Klebsiella has emerged globally and is now a major cause of severe infections, particularly in immuno-compromised patients ( Lee et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We presumed that this isolate was allochthonous, indicating its origin was probably associated with contaminated water from sewage or other waste-water sources. It is known that so called super-bugs, such as the carbapenem-and extended spectrum betalactamase-resistant Klebsella pneumoniae, as isolated in this case, are widespread throughout health care facilities and are bacteria causing hospital infections [26]. Such multi-resistant bacteria, particularly carbapenemase-producing Enterobacteriaceae, are well-known as widespread nosocomial infectious agents in Lithuania [27].…”
Section: Discussionmentioning
confidence: 99%
“…To date, ESBL-producing K. pneumonia contributes to nearly 45% of K. pneumoniae nosocomial infections ( Miftode et al, 2021 ) and 43% in the intensive care unit ( Paterson et al, 2004 ; Calbo et al, 2011 ). More strikingly, ESBL-positive strains result in significantly higher mortality ( Miftode et al, 2021 ); a recent study reported that ESBL-producing K. pneumonia is associated with over 55% mortality ( Starzyk-Luszcz et al, 2017 ). Despite various genes encoding ESBLs, most ESBLs were derived from one or two amino acid substitutions of SHV-1 and TEM-1 ( Ramdani-Bouguessa et al, 2011 ; Ben Achour et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%